Perceptual and quantitative analysis of discoloration of orthodontic elastomeric chains by food - Hyun-Joo Chung; Sun-Ah Lim; Ho-Kyung Lim; Seok-Ki Jung (BMC, 2023)
Abstract Background The objectives of this study were to use a digital camera to measure the discoloration of orthodontic elastomeric chains in various immersion solutions over different time periods and to determine the valid acceptability tolerances for color changes in orthodontic elastomeric chains by surveying digital photographs. Methods Orthodontic elastomeric chains were applied to the maxillary anterior teeth of nine typodont models. The models were divided into three groups and immersed in the curry, coffee, and wine solutions. The digital images of the elastomeric modules were captured and processed using commercial software after 30 min of immersion, thrice a day, for 28 days. The differences in color changes ( $$Δ {\text{E}}$$ Δ E ), depending on the type of immersion solution and period, were analyzed using a repeated-measures analysis of variance (ANOVA) test. A web-based survey questionnaire was randomly distributed to 50 respondents for a visual analysis of the elastomeric chain discoloration. The relationship between the surveying score and $$Δ {\text{E}}$$ Δ E value was analyzed using Spearman's correlation coefficient. The perceptibility and acceptability of elastomeric chain discoloration ( $$Δ {\text{E}}$$ Δ E ) based on the type of immersion solutions and periods were analyzed using a regression model. Results Significant differences were observed in the discoloration of the elastomeric power chain depending on the immersion solution and period. The amount of discoloration was highest in curry, followed by coffee and wine (P < 0.05). The mean discoloration ( $$Δ {\text{E}}$$ Δ E ) continued to increase over the entire immersion period. There was a significant correlation between visual scoring and discoloration ( $$Δ {\text{E}}$$ Δ E ) over the entire period, especially in the early stages compared to the later stages (r = 0.918, P < 0.05). In 50% of the respondents, the predicted clinically unacceptable discoloration was between 4.46 and 9.98 and in 90% of the respondents, it was between 16.52 and 19.85. Conclusions The amount of discoloration was the highest for curry, followed by coffee and wine, and continued to gradually increase during the observation period. Significant differences were found between the color measurements obtained and the visual assessment by observers. The observers varied in their tolerance for perceptibility and acceptability for elastomeric chain discoloration based on the type of dietary media.